IN VITRO DIGESTIBILITY ANALYSIS OF FERMENTED RICE STRAW USING ASPERGILLUS NIGER AND EFFECTIVE MICROORGANISMS - Darmawansya, Muhammad; Sandiah, Natsir; Nasiu, Firman (Pascasarjana Universitas Sulawesi Tenggara, 2021)
This research aims to determine the in vitro digestibility of rice straw fermented with Aspergillus niger and Effective Microorganisms 4(EM-4). The design used in this study used a completely randigestibility organic matter ized design consisting of 4 treatments and each treatment consisting of 3 replications, so that there were 12 experimental units. The treatment consists of P0 (unfermented rice straw), P1 (fermented EM-4 rice straw), P2 (Aspergillus niger fermented rice straw) and P3 (Aspergillus niger fermented rice straw and EM-4). The variables observed were digestibility of organic matter, digestibility of dry matter and digestibility of crude fiber. Observation data were analyzed using ANOVA analysis of variance (analysis of variance) and Duncan's advanced test. The results showed that Fermented rice straw using EM-4, Aspergillus niger and a combination of both, can improve digestibility of organic matter, digestibility of dry matter and digestibility of crude fiber in vitro, where The highest increase in digestibility occurred in the combination treatment between EM-4 and Aspergillus niger.